Caractérisation De La Flore Et De La Végétation Ligneuse Des Terroirs Villageois De Keur Birame (Kaffrine) Et Saré Yorobana (Kolda) Au Sénégal - Diedhiou, Mamadou Abdoul Ader; Faye, Elhadji; Ngom, Daouda; Fall, Saliou (European Scientific Journal, ESJ, 2018)
Vegetation in sub-Saharan countries is under heavy pressure from anthropogenic activities and climatic deterioration. This study was carried out at Keur Birame and Saré Yorobana villages, which are two edaphoclimatically contrasting localities. The aim of this study is to characterize their flora and woody vegetation. In doing so, 178 vegetation survey of 2500m² each were carried out on all two sites consisting of nine facies of vegetation. The results show a flora of the two soils of 93 species belonging to 80 genera and distributed to 33 botanical families. Among this richness, 78 species belong to Saré Yorobana and 45 species to Keur Birame. Except for regeneration rates (37.30% and 94.04%), all structural parameters studied are higher at Saré Yorobana and the similarity index (0.48) indicates that the two vegetal communities are floristically different. The ligneous stems are generally young with small diameter that hides facies imbalances due to human activities. It would require the various actors synergy to keep trees and biodiversity in the fields and terroirs.